2005
DOI: 10.1111/j.1439-037x.2005.00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Putrescine Increases Floral Retention, Pod Set and Seed Yield in Cold Stressed Chickpea

Abstract: Chickpea (Cicer arietinum L.) is sensitive to cold stress (<8°C) at its reproductive phase that results in flower abortion, poor pod set and thus reduced yield. Early maturing genotypes are especially more sensitive. In this crop, the metabolic causes underlying cold injury that are imperative to induce cold tolerance are not known. In the present study, the endogenous levels of putrescine (diamine), spermidine (triamine) and spermine (tetramine) were examined in early maturing chickpea genotype ICCV 96029, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…PAs exert influence in the plant life cycle, including cell division and elongation, morphogenesis, seed germination, flowering, and senescence (Igarashi and Kashiwagi, 2000;Bais and Ravishankar, 2002;Yoda et al, 2006;Wimalasekera et al, 2011;Gupta et al, 2013). Furthermore, PAs also have impact on plants in response to diverse abiotic stresses, such as salinity (Zapata et al, 2004;Shu et al, 2012), drought (Yang et al, 2007;Li et al, 2015), oxidative stress (Rider et al, 2007;Puyang et al, 2015), high temperature Mostofa et al, 2014), and chilling stress (Nayyar, 2005;Yamamoto et al, 2012). It was previously suggested that the elevated stress tolerance of plants due to PAs may be attributed to their polycationic nature at physiologic pH.…”
Section: Introductionmentioning
confidence: 99%
“…PAs exert influence in the plant life cycle, including cell division and elongation, morphogenesis, seed germination, flowering, and senescence (Igarashi and Kashiwagi, 2000;Bais and Ravishankar, 2002;Yoda et al, 2006;Wimalasekera et al, 2011;Gupta et al, 2013). Furthermore, PAs also have impact on plants in response to diverse abiotic stresses, such as salinity (Zapata et al, 2004;Shu et al, 2012), drought (Yang et al, 2007;Li et al, 2015), oxidative stress (Rider et al, 2007;Puyang et al, 2015), high temperature Mostofa et al, 2014), and chilling stress (Nayyar, 2005;Yamamoto et al, 2012). It was previously suggested that the elevated stress tolerance of plants due to PAs may be attributed to their polycationic nature at physiologic pH.…”
Section: Introductionmentioning
confidence: 99%
“…During vegetative growth PAs have been shown to reduce the accumulation of Na + , alleviate the loss of K + , reduce ROS accumulation and enhance the activity of antioxidative enzymes and non-enzymatic antioxidants, alleviate chlorophyll loss and membrane leakage, and increase compatible osmolytes (Chattopadhayay et al, 2002;Roy et al, 2005;Ndayiragije and Lutts, 2006;Quinet et al, 2010;Roychoudhury et al, 2011;Saleethong et al, 2011). Exogenous application of PAs has also been reported to promote reproductive development and offers protection to reproductive structures leading to yield improvement under cold stress in chickpeas (Nayyar, 2005) and salt stress in rice (Ndayiragije and Lutts, 2007;Saleethong et al, 2013). However, the effects of exogenous PAs on the nutritional quality of harvested seeds were not addressed in previous studies.…”
mentioning
confidence: 99%
“…As putrescine accumulation reduced the chilling injury in tomato (Solanum lycopersicum L.) (Kim et al, 2002), chickpea (Cicer arietinum L.) (Nayyar, 2005) and maize (Cao et al, 2008) under chilling stress. Many studies demonstrated that genetic modification of the polyamine biosynthetic pathway is a useful tool to recognize the function of polyamines in plant responses to abiotic stresses in both crops and model plants (Igarashi and Kashiwagi, 2000;Childs et al, 2003;Kusano et al, 2008).…”
Section: Discussionmentioning
confidence: 99%